An exploratory study of motivations in the Civic Welfare Training Service (CWTS) program of the National College of Public Administration and Governance (NCPAG) - Falogme, Marijune C.; Lim, Reynaldo Ronwaldo S., Jr; Pallingayan, Margel Karen V.; Palmes, Doha D. ([National College of Public Administration and Governance, University of the Philippines Diliman], 2004)
This study investigated what motivates "mandatory volunteers", both the adviser and students of the National College of Public Administration and Governance (NCPAG), to participate in the National Service Training Program (NSTP) particularly the Civic Welfare Training Service (CWTS). These motivations are regarded as important factors for the success of the program. The adviser was interviewed regarding the program itself and the tasks and responsibilities involved. This study also surveyed students from NCPAG enrolled in CWTS. Two focus group discussions (FGDs) were also conducted among the respondents to detail their experiences and to ascertain what factors motivated them the most. Herzberg's Motivation-Hygiene Theory was used to classify these factors that affect the students' job satisfaction and dissatisfaction. This study showed that hygiene factors are regarded as highly important factors in increasing the level of motivation of mandatory volunteer in CWTS.